Determination of distance advanced by the waterfront in a border strip land using Laplace transformation. (6th January 2021) - Hasan, Mahbub; Kassu, Aschalew
Among various methods of surface irrigation, border method is widely applicable to cultivate most cereal crops like wheat, maize etcetera and rice (Amiri et al., 2016). The waterfront advance data has to be synchronised with the infiltration depth, especially at the head end along with the consideration of sufficiency of infiltrated depth of water at the tail end. With that point of view, this study was undertaken to calculate the waterfront advance distance from the head end using Laplace transformation. Values for the constants for infiltration equation were collected and used in the Laplace transformation equations and found to match the calculated and actual waterfront advance data with a very reasonable discrepancy. The actual waterfront distance was only 0.51 m shorter than that was calculated by Laplace transformation. This might have caused due to soil cover, irregular tillage operation, huge potholes, and discontinuation of the uniformity of slope of the border strip. Application of this method will help to increase the water application efficiency with respect to flow size, border strip slope, depth of water requirement infiltrated in certain time to meet the crop water requirement.